Integration of Local Wisdom Values “Domyak Ritual” in Character Education - Anggy Giri Prawiyogi; Retno Dwimarwati; Suhendi Afryanto; Muh. Erwinto Imran (Indonesia Approach Education, 2023)
This research aims to examine the process in the Domyak Ritual and the values ​​contained therein, that can be integrated into character education in Indonesia’s schools. The method used is a descriptive qualitative method with an ethno pedagogic approach. Data collection techniques used in this study were literature review, interview, observation and documentation. The results of the study can be explained, that the Domyak Ritual was born in 1920 and initially as a ritual ceremony requesting for rain. In the Domyak Ritual there are four parts, namely preparation, gending tatalu (activities hitting musical instruments), ngado’a (pray), and entertainment of various kinds of arts. The values ​​contained in the Domyak Ritual are an attitude of responsibility, always starting activities with prayer, always maintaining community harmony and always keeping oneself and the environment clean. Therefore, the values ​​contained in the Domyak Ritual are expected to be integrated into character education in schools.